Hemoparasites present in feral populations of rock dove (Columba livia) in the department of Lima, Peru - Carlos Erazo, Nancy (2017)
The aim of the study was to determine the presence of blood parasites in feral populations of the rock dove (Columba livia) in the department of Lima, Peru. The study was carried out in Pampas San Alejo, located in Barranca (rural area) and in a zoo located in San Juan de Miraflores district (urban area). A total of 52 adult birds were captured using mist nets, resulting 28 and 24 pigeons in the rural and urban area respectively. Blood samples from the brachial vein were collected, and blood smears were fixed with methanol and stained with Giemsa. Results showed 94.2% (49/52) positive to the presence of hemoparasites: Haemoproteus sp (94.2%; 47/52), Plasmodium sp (13.5%; 7/52) and Leucocytozoon sp (1.9%; 1/52). The Haemoproteus sp infestation intensity was very low (24.5%), low (59.2%) and medium (16.3%). All rural birds were positive, while only 87.5% (21/24) of birds in the urban area had hemoparasites, although this difference was not significant.